ANALISIS SIKAP MENTAL MAHASISWA DALAM BERWIRAUSAHA - NURVI OKTIANI (Cakrawala - Jurnal Humaniora, 2015)
This research purposes to identificate the mentality of student attitudes toward build entrepreneur.Background of this research are there is matter how to understand and improve the mentality of Student attitude toward entrepreneurship, where they still considered the main of important to build entrepreneurship is capital. That can describe the dominant factors much influence for all of the student.The Results for this research are intrepretation for mentality attitude to build entrepreneurship consist of the average of visioner is 4.37, creativity and inovative is 3.91, can make opportunity is 3.79, leadership is 4.02, and self confidence is 3.8. it can describe, it is still under average about some of student attitudes toward build entrepreneurship, it is especially creativity and inovative, can make opportunity, self confidence, so the solution is make understanding for all of student that one of important thing for growing entrepreneurship that build the high mental capability.Keyword: attitude toward, entrepreneurship